Decreasing viscosity and increasing accessible load by replacing classical diluents with a hydrotrope in liquid–liquid extraction - Asmae El Maangar; Thomas Zemb; Clément Fleury; Jean Duhamet; Jean-François Dufrêche; Stéphane Pellet-Rostaing (Frontiers in Chemical Engineering)
Using a generic example, we show that the strategy of replacing a classically used aliphatic diluent with a hydrotrope in liquid–liquid extraction induces higher performance. Liquid–liquid extraction is widely used in hydrometallurgical processes for recycling strategic metals, but it is limited due to the formation of a third phase. Hydrotropes have never been studied as diluents in the context of metal recycling. We show that using hydrotropes as a diluent decreases the viscosity of solutions by more than a factor of ten, even under high load by extracted cations. It also increases the efficiency of extraction for typical ionic extractants such as anionic phosphates or non-ionic amides. The latter also quench all types of third-phase transition that occur when classical diluents are used. The gain in distribution coefficient by a factor of ten comes from the entropy of the solvent phase involved and is not linked to apparent complexation constants. In the case of anionic extractants, the Gibbs energy of transfer depends linearly on the ionic radii of the rare earth considered, which is not true with non-ionic extractants. Moreover, the maximum load possible is increased by a factor of two to three versus alkanes, allowing more compact design and intensification of extraction processes. Based on SAXS and surface tension measurements, the origin of this gain in Gibbs energy of transfer and tunable selectivity in the family of rare earth elements is further identified by three mechanisms: reduction of the term linked to complexation, more than compensated by a synergistic effect of the hydrotrope and the comlexant, and the intra-aggregate entropy of mixing. The result is a systematic increase of distribution coefficient of the order of 50–150 of the distribution coefficients, induced systematically by the replacement of alcanes with hydrotropes as diluents.